May-Thurner Syndrome: a case report after two years of endovascular treatment - Soares,Tony R. (2018)
Previously considered a rare clinical condition, the development of more sophisticated imaging methods and endovascular intervention for deep venous thrombosis (DVT) led to a more frequent identification of May-Thurner Syndrome. We present a 68 years-old woman with history of chronic pain and edema in the left lower limb and a CT-scan finding of left common iliac vein compression. Phlebography confirmed a stenosis in the confluence of the left common iliac vein with the inferior vena cava and a dilated left ovarian vein as well as voluminous collaterals in the pelvic fossa to the contralateral iliac vessels. These aspects are suggestive of May-Thurner Syndrome. The lesion was treated by venous angioplasty and stenting of the left common iliac vein. The recovery was uneventful, the patient remained on antiplatelet therapy and anticoagulation and had a notorious clinical improvement. May-Thurner Syndrome should be suspected in patients with chronic symptoms of venous insufficiency or as an underlying cause of acute proximal DVT in the left lower limb.